Hardware and software structure for hosting and executing autonomous behavior routines in unmanned aerial vehicles - Araya Castillo, Pablo Andrés (2020)
The Integrated Group for Engineering Research (GII) is an R & D group from the University of A Coruña that has a research line of unmanned aerial vehicles (UAV). They have worked on multiple applications with UAVs using the Pixhawk autopilot. The vehicles receive instructions from a remote control while sends flight status information to a ground control station (GCS), a computer to visualize what is happening during the execution of a mission.However, the UAVs were unable to perform tasks that involved autonomous behavior, and the communication with the GCS was not fluid enough to visualize the flight correctly.To solve the problem, a functionally flexible hardware and software structure was implemented in a UAV, which included a mini PC on board in which autonomous and non-autonomous flight routines can be programmed, which give the Pixhawk instructions directly. In addition, a GCS displays the flight status with more fluid communication and the decisions taken by the vehicle.The correct performance of the structure was verified through simulations and validated with an autonomous test flight, in which the UAV decided and executed its own route according to the conditions of the programmed mission.